2016
DOI: 10.5539/jfr.v5n3p92
|View full text |Cite
|
Sign up to set email alerts
|

Meat Colour Stability and Fatty Acid Profile in Commercial Bison and Beef

Abstract: Commercial bison meat has been found to discolour more rapidly than beef in retail display. The influence of fat content, fat composition and vitamin E on the colour stability of commercially produced bison and beef were examined. Longissimus samples from grain-fed beef (n = 20) and grass-fed bison (n = 14) were analyzed for fat content, fatty acid composition, vitamin E levels, pigments, TBARS and retail stability. Intramuscular fat content was lower and richer in PUFA in bison (P < 0.01) compared to beef. Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The total tocopherol concentration from the meat averaged 1.13 µg × g -1 (range: 0.66 to 2.47 µg × g -1 ). This is low relative to the concentrations found in meat from grass fed bison (3.47 µg × g -1 ) and grain finished beef (2.20 µg × g -1 ; Galbraith et al, 2016). In lamb, concentrations of vitamin E in muscle below 3 µ × g -1 has resulted in a higher rates of lipid oxidation (Ponnampalam et al, 2014).…”
Section: Fatty Acid and Proximate Composition Of Bison Loin And Burgersmentioning
confidence: 84%
“…The total tocopherol concentration from the meat averaged 1.13 µg × g -1 (range: 0.66 to 2.47 µg × g -1 ). This is low relative to the concentrations found in meat from grass fed bison (3.47 µg × g -1 ) and grain finished beef (2.20 µg × g -1 ; Galbraith et al, 2016). In lamb, concentrations of vitamin E in muscle below 3 µ × g -1 has resulted in a higher rates of lipid oxidation (Ponnampalam et al, 2014).…”
Section: Fatty Acid and Proximate Composition Of Bison Loin And Burgersmentioning
confidence: 84%
“…The rapid discoloration of bison meat could not be attributed to a difference in the biochemistry of bison myoglobin (Mb) per se (identical amino acid sequences and similar oxidation kinetics and thermostability) (Joseph et al, 2010). However, bison have been shown to have a difference in muscle fibre type (Koch et al, 1995;Aalhus et al, 2009), resulting in higher pigment concentration (Galbraith et al, 2016) and higher levels of iron (Marchello and Driskell, 2001;Galbraith et al, 2006) compared with those typically found in beef. In addition, polyunsaturated fatty acid levels (weight percentage) in range-fed and feedlot-fed bison were found to be higher than in range-or feedlot-fed cattle (Rule et al, 2002).…”
Section: Introductionmentioning
confidence: 99%